FINANCIAL INCLUSION, ECONOMIC GROWTH AND POVERTY IN INDONESIA WITH PANEL SIMULTANEOUS MODELS APPROACH - Almasah, Munifah Zuhra; Sirait, Timbang (PATTIMURA UNIVERSITY, 2023)
Financial inclusion is a condition that people have equal access to and use financial services. However, in 2021, Indonesia will have the fourth-highest proportion of unbanked citizens worldwide. Economic growth may have an indirect or direct impact on poverty depending on financial inclusion. Several variables that encourage financial inclusion have been described by many studies. This study aims to analyze simultaneous equation models using panel data of financial inclusion, then identify its causality relationship with economic growth and poverty of 33 provinces in Indonesia from 2011-2021. As result, only the variable mean years of school has an effect on increasing of financial inclusion index. The three variables of economic development, namely financial inclusion, economic growth, and poverty have a one-way causality relationship. That is means there has been no visible development synergy in terms of financial inclusion, economic growth, and poverty. It could be an example given to the government in evaluating Indonesia's regional development gap.